An Analysis and Design for Nonlinear Quadratic Systems Subject to Nested Saturation. (30th September 2013) - Zhang, Minsong; Chen, Fu
Abstract : This paper considers the stability problem for nonlinear quadratic systems with nested saturation input. The interesting treatment method proposed to nested saturation here is put into use a well-established linear differential control tool. And the new conclusions include the existing conclusion on this issue and have less conservatism than before. Simulation example illustrates the effectiveness of the established methodologies.